Ocular hypotensive effects of angiotensin II type 1 receptor blockers in rat model of steroid induced ocular hypertension / Siti Nur Laili Mohamed - Mohamed, Siti Nur Laili (2013)
Glaucoma is associated with elevated intraocular pressure (IOP). As angiotensin II type 1 receptor blocker (ARB) has been shown to have oculohypotensive effect on rats with normal intraocular pressure, in this study we evaluated the IOP lowering effects of ARB in steroid-induced oculohypertensive rats. We also studied the effects of ARB on trabecular meshwork (TM) remodeling.